Supplementation With Chinese Medicinal Plant Extracts From Lonicera hypoglauca and Scutellaria baicalensis Mitigates Colonic Inflammation by Regulating Oxidative Stress and Gut Microbiota in a Colitis Mouse Model - Wan, Fan; Wang, Mengyu; Zhong, Ruqing; Chen, Liang; Han, Hui; Liu, Lei; Zhao, Yong; Lv, Huiyuan; Hou, Fujiang; Yi, Bao; Zhang, Hongfu (Frontiers in Cellular and Infection Microbiology, 2022)
Colitis, a chronic inflammatory bowel disease, is characterized with bloody diarrhea and inflammation in the colon. Lonicera hypoglauca (“Shanyinhua” in Chinese) and Scutellaria baicalensis (“Huangqin” in Chinese) are two traditional Chinese medicinal plants rich in polyphenols, such as chlorogenic acid (CGA) and baicalin (BA), with the effects of anti-inflammation and antioxidation. However, it remains unknown whether extracts from Lonicera hypoglauca and Scutellaria baicalensis (LSE) could mitigate colonic inflammation. In the present study, ICR mice (22.23 ± 1.65 g) were allocated to three groups treated with chow diet without (CON) or with DSS (CON + DSS) in water or LSE supplementation in diet with DSS (LSE + DSS), and then inflammatory, oxidative parameters and colonic microbiota were detected. The results showed that LSE (500 mg/kg) treatment mitigated DSS-induced colitis symptoms, and restored the shortened colon length, the increased disease activity index (DAI), and the damaged intestinal barrier. In serum, LSE supplementation significantly decreased levels of pro-inflammatory cytokines including interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and lipopolysaccharide (LPS) and increased IL-10 level. Meanwhile, superoxide dismutase (SOD) and catalase (CAT) were increased, and malondialdehyde (MDA) and reactive oxygen species (ROS) levels were decreased. In the colon tissue, qPCR results showed that LSE supplementation dramatically downregulated transcriptional expression of IL-1β, IL-6, TNF-α, and MDA as well as upregulated the expression of SOD1, CAT, and IL-10. Additionally, the damaged gut barrier Occludin and zona occludens-1 (ZO-1) in the CON + DSS group was enhanced with LSE supplementation. Furthermore, LSE treatment regulated the gut microbial communities with higher relative abundances of Dubosiella and Ruminococcus torques group, and lower relative abundance of Bacteroides and Turicibacter. Moreover, the contents of short-chain fatty acids (SCFAs) as products of gut microbiota, were also increased. Correlation analysis showed that the mRNA expression of SOD1 was negatively correlated with TNF-α (r = -0.900, P < 0.05); the mRNA expression of IL-6 (r = -0.779, P < 0.05) and TNF-α (r = -0.703, P < 0.05) had dramatically negative correlation with Dubosiella. In conclusion, LSE supplementation could effectively ameliorate inflammation by modulating oxidative stress and gut microbiota in a colitis mouse model.